Oropharyngeal Microbiota in Frail Older Patients Unaffected by Time in Hospital - Ewan, Victoria C.; Reid, William D. K.; Shirley, Mark; Simpson, A. John; Rushton, Steven P.; Wade, William G. (Frontiers in Cellular and Infection Microbiology, 2018)
Respiratory tract infections are the commonest nosocomial infections, and occur predominantly in frailer, older patients with multiple comorbidities. The oropharyngeal microbiota is the major reservoir of infection. This study explored the relative contributions of time in hospital and patient demographics to the community structure of the oropharyngeal microbiota in older patients with lower limb fracture. We collected 167 throat swabs from 53 patients (mean age 83) over 14 days after hospitalisation, and analysed these using 16S rRNA gene sequencing. We calculated frailty/comorbidity indices, undertook dental examinations and collected data on respiratory tract infections. We analysed microbial community composition using correspondence (CA) and canonical correspondence analysis. Ten patients were treated for respiratory tract infection. Microbial community structure was related to frailty, number of teeth and comorbidity on admission, with comorbidity exerting the largest effect. Time in hospital neither significantly changed alpha (t=-0.846, p=0.399) nor beta diversity (CA1 t=0.022, p=0.982; CA2 t=-0.513, p=0.609) of microbial communities in patient samples. Incidence of respiratory pathogens were not associated with time in hospital (t=-0.207, p=0.837), nor with alpha diversity of the oral microbiota (t=-1.401, p=0.164). Patient characteristics at admission, rather than time in hospital, influenced the community structure of the oral microbiota.